Answer:
x = √39
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
<u>Trigonometry</u>
- [Right Triangles Only] Pythagorean Theorem: a² + b² = c²
Step-by-step explanation:
<u>Step 1: Identify</u>
Leg <em>a</em> = <em>x</em>
Leg <em>b</em> = 5
Hypotenuse <em>c</em> = 8
<u>Step 2: Solve for </u><em><u>x</u></em>
- Substitute [PT]: x² + 5² = 8²
- Isolate <em>x</em> term: x² = 8² - 5²
- Exponents: x² = 64 - 25
- Subtract: x² = 39
- Isolate <em>x</em>: x = √39
Answer:
(x+2) (x+3) (x-5)
Step-by-step explanation:
x³-19x-30 = (x+2) (x²+ax-15) ... x³=x*(1*x²) while -30= (2)*(-15)
x³ +<u> 0</u>*x² - 19x -30 = x³ + (<u>2+a</u>)x² + (2a-15)x -30
2+a = 0
a = -2
x³-19x-30 = (x+2) (x²-2x-15) = (x+2) (x+3) (x-5)
I think the mode is 9.875
Answer:
2/5
Step-by-step explanation:
The answer is common sense.
Answer:
-9π
Step-by-step explanation:
∫c (4y dx + 2xy dy)
= ∫∫ [(∂/∂x)(2xy) - (∂/∂y)(4y)] dA, by Green's Theorem
= ∫∫ (2y - 4) dA
Now convert to polar coordinates:
∫(r = 0 to 3) ∫(θ = 0 to 2π) (2r sin θ - 4) * (r dθ dr) --- first integration
= ∫(r = 0 to 3) (-2r cos θ - 4θ) * r {for θ = 0 to 2π} dr
= ∫(r = 0 to 3) -2πr dr
= -πr² {for r = 0 to 3}
= -π(3²) - -π(0)²
= -9π